Accidents Analysis in Sugar Factories: Causes Using Government Regulation and Human Factor and Classification System (HFACS) - Santoso, Edi; Kurniasih, Dewi; Nugroho, Priyambodo Nur Ardi (Formosa Journal of Science and Technology, 2024)
The Sugar Factory uses more than 150 pieces of equipment in production process. With so many tools, the possibility of accidents also very large, especially because of the age of mechine and equipment. On July 22 2022, an accident occurred which resulted 1 (one) person dying as a result of being hit by a lifting beam and sugarcane scale due to a broken wire rope. Investigation and analysis of the causes of accidents as well as follow-up actions must be carried out, because the production process must continue. This research aims to analyze accidents that occur based on human factors using Government Regulation and Human Factor Analysis and Classification System (HFACS) approach. Government regulations are used to identify the types of accidents with a major impact on lost work hours and fatalities. Government regulations are used to determine the types of accidents that have a major impact on lost work hours and deaths. Using data from sugar factories and interview results, this study shows that accidents with the greatest impact are caused by lifting equipment. Using the Human Factor And Classification System (HFACS) method to analyze the 6 accidents, the results show that at level 1, the biggest causes of accidents are at the sub-level decision error, skill-based error, perceptual error and routine violation. At level 2, the biggest causes of accidents are at the sub-level technological environment and personal readiness. While at levels 3 and 4, Failed to correct problem and supervisory violation have the largest percentage at level 3 and resource management at level 4. The conclusion shows that there are still various problems from the human factor to implementate occupational safety which could potentially lead to accidents.